Developing English Learning Model Project Based Content And Language Integrated Learning (Clil) For English At University Level In Indonesia - ., Huzairin; ., Sudirman; Hasan, Basturi (Advances in Social Sciences Research Journal, 2018)
This study explores project based content language integrated learning (CLIL) executed at a higher education insitution in Lampung Indonesi. The research was proposed based on a mixture of the principle of language integrated learning (CLIL) and the principle of project based learning. The design was implemented for the teaching of English as a compulsory subject at Istitute of Technology Sumatera. Quantitative data was obtained from the teaching before and after CLIL model application. While the qualitative data was obtained from the output of language produced by students during the learning process took place The results showed that project based CLIL English language course at the Istitute of Technology Sumatera could work effectively.